STUDY THE EFFECTIVENESS OF ANTIVIRAL TREATMENTS IN PREVENTING EPISODES OF HEPATIC DECOMPENSATION IN CHRONIC HEPATITIS PATIENTS WITH DECOMPENSATED CHRONIC LIVER DISEASE - Dr Amina Saliha; Dr Shanza Zafar; Dr Aatka Rauf; Dr Aiza Rao; Dr Aasma Ismail; Dr Palwasha Shabbir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Chronic hepatitis B and decompensated chronic liver disease (DCLD) are significant medical conditions worldwide, with a tendency to cause hepatic decompensation in most cases. Antiviral therapy is a crucial intervention in hepatic decompensation and enhancement in prognosis in patients with CHB and DCLD.Objective: To determine the effectiveness of antiviral therapy in preventing hepatic decompensation in patients with chronic hepatitis B and decompensated cirrhosis.Study Design: Quasi-experimental study.Duration and Place of Study: The study was conducted between August 2023 and June 2024 at the Department of Gastroenterology.Methodology: A total of 191 patients aged ≥18 years with chronic hepatitis B and decompensated cirrhosis were enrolled. Patients received either Entecavir (ETV) or Tenofovir (TDF) as antiviral therapy. Efficacy was defined by the prevention of hepatic decompensation episodes, including ascites, variceal bleeding, hepatic encephalopathy, and spontaneous bacterial peritonitis (SBP). Data on demographic, clinical, and laboratory parameters were recorded.Results: The study found that antiviral treatment was effective in preventing hepatic decompensation in 60.2% of patients. Tenofovir demonstrated superior efficacy (76.4%) compared to Entecavir (53.7%) (p=0.004). Significant predictors of efficacy included INR levels (Exp(B)=0.208, p=0.014) and the type of treatment (Tenofovir vs Entecavir) (Exp(B)=2.432, p=0.022).Conclusion: Antiviral therapy, and Tenofovir in particular, can effectively reduce hepatic decompensation in cirrhotic and HBV-related chronic hepatitis B infection patients. INR is a key predictive indicator for successful therapy.